Dylematy i konflikty moralne polityków i lekarzy w ustanawianiu zadań systemu opieki zdrowotnej - Gałuszka, Mieczysław (Annales. Etyka w Życiu Gospodarczym, 2008)
Medicine is the field of knowledge and set of clinical practices, characterized by the presence ofpolitics and ethics on all the levels. Politics should be treated as a domain of power, which aims to makestrategic decisions concerning health of the citizens leading to form socially accepted objectives ofhealth care policy. Ethics sets axiological frames for morally just decisions both political and medicalin the field of health care.The article analyzes the reasons of conflicts and moral dilemmas in the health care system.Decisions which are made within health care system should accomplish five criteria: medical,economical, social, legal and axiological. The term “moral panic” is used to illustrate situationsconcerning corruption and moral atrophy of doctors.